PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS PROBLEM BASED LEARNING BERBANTUAN MACROMEDIA FLASH UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH - Novalisa Pratiwi; Yarman Yarman (UNIVERSITAS MUHAMMADIYAH METRO, 2024)
This research was motivated by the suboptimal ability to solve mathematical problems of class VIII junior high school students.This research aims to produce learning tools in the form of lesson plans and worksheet based on problem based learning assisted by macromedia flash to improve students' mathematical problem solving abilities that are valid, practical and effective. This research is development research with a pilot model which consists of preliminary research, prototyping phase, and assessment phase. This research was conducted at Atthayyibah Kerinci Middle School. The results of the research show that the problem based learning tool with the help of Macromedia Flash that was developed is classified as very valid based on the expert review for the RPP, which is 3.77 and LKPD is 3.68. Meanwhile, the practicality results were 90.11% and 89.75% with very practical criteria. Apart from that, the effectiveness of the percentage of completeness of students who took the mathematical problem solving ability test for the small group stage obtained a complete percentage of 80.65% and at the field test stage obtained a complete percentage of 86.49% so it was categorized as effective. So it can be concluded that the learning tool based on problem based learning assisted by Macromedia Flash on relationship and function material is said to be valid, practical and effective.